Large‐Scale Synthesis of Spinel NixMn3‐xO4 Solid Solution Immobilized with Iridium Single Atoms for Efficient Alkaline Seawater Electrolysis. Issue 16 (27th March 2022) - Wen, Ning; Xia, Yuguo; Wang, Haihua; Zhang, Dongpeng; Wang, Haimei; Wang, Xiang; Jiao, Xiuling; Chen, Dairong
Abstract: Seawater electrolysis not only affords a promising approach to produce clean hydrogen fuel but also alleviates the bottleneck of freshwater feeds. Here, a novel strategy for large‐scale preparing spinel Nix Mn3‐x O4 solid solution immobilized with iridium single‐atoms (Ir‐SAs) is developed by the sol–gel method. Benefitting from the surface‐exposed Ir‐SAs, Ir1 /Ni1.6 Mn1.4 O4 reveals boosted oxygen evolution reaction (OER) performance, achieving overpotentials of 330 and 350 mV at current densities of 100 and 200 mA cm –2 in alkaline seawater. Moreover, only a cell voltage of 1.50 V is required to reach 500 mA cm –2 with assembled Ir1 /Ni1.6 Mn1.4 O4 ‖Pt/C electrode pair under the industrial operating condition. The experimental characterizations and theoretical calculations highlight the effect of Ir‐SAs on improving the intrinsic OER activity and facilitating surface charge transfer kinetics, and evidence the energetically stabilized *OOH and the destabilized chloride ion adsorption in Ir1 /Ni1.6 Mn1.4 O4 . This work demonstrates an effective method to produce efficient alkaline seawater electrocatalyst massively. Abstract : Exploring rational strategy for large‐scale synthesis of OER electrocatalysts with high activity and structural robustness is essential to achieve industrial seawater electrocatalysts. In this work, mass‐productive Nix Mn3‐x O4 solid solution immobilized with iridium single‐atoms reveals excellent OER activity and anti‐chloride corrosion characteristics, rendering it a promising seawater electrocatalyst.